Black Brilliance and Creative Problem Solving in Fugitive Spaces: Advancing the BlackCreate Framework Through a Systematic Review. Issue 1 (March 2022) - Mims, Lauren C.; Rubenstein, Lisa DaVia; Thomas, Jenna
Traditional definitions and assessments of creativity often neglect to identify the complexity surrounding Black students' brilliance, leading to lack of access and funding. Further, even when recognized, Black students are often funneled into programs that do not facilitate positive development of their racial-ethnic identity. Through our systematic review of 155 publications, we developed the BlackCreate Framework to illustrate how effective Black creative educational experiences (BCEEs) create fugitive spaces for creative expression and education. Within these spaces, both societal oppression and community assets are explicitly discussed as a part of the creative process, providing students methods for adaptive coping and for addressing systemic inequities. Given these findings, we advocate for consistent funding and support for fugitive spaces to promote Black students' creativity.